Platelet‐rich plasma improves the therapeutic efficacy of mesenchymal stem cells by enhancing their secretion of angiogenic factors in a combined radiation and wound injury model. Issue 2 (18th November 2019) - Myung, Hyunwook; Jang, Hyosun; Myung, Jae Kyung; Lee, Changsun; Lee, Janet; Kang, JiHoon; Jang, Won‐Suk; Lee, Sun‐Joo; Kim, Hyewon; Kim, Hwi‐Yool; Park, Sunhoo; Shim, Sehwan
Abstract: Delayed wound healing after radiation exposure can cause serious cutaneous damage, and its treatment is a major clinical challenge. Although mesenchymal stem cells (MSCs) have emerged as a promising therapeutic agent in regenerative medicine, they alone do not produce satisfactory effects in a combined radiation and wound injury (CRWI) model. Here, we investigated the therapeutic effect of combined umbilical cord blood‐derived (UCB)‐MSCs and platelet‐rich plasma (PRP) treatment on wound healing in a CRWI mouse model. First, we assessed the release of cytokines from UCB‐MSCs cultured with PRP and observed changes in the expression of angiogenic factors. The angiogenic paracrine factors from UCB‐MSCs cultured with PRP were assessed in human umbilical vein endothelial cells (HUVECs). To assess therapeutic efficacy, UCB‐MSCs and PRP were topically implanted into a CRWT mouse model. Vascular endothelial growth factor (VEGF), a pro‐angiogenic growth factor, urokinase‐type plasminogen activator and contributor to VEGF‐induced signalling were more highly expressed in conditioned media of UCB‐MSCs cultured with PRP than in that of UCB‐MSCs alone. Furthermore, conditioned media of UCB‐MSCs cultured with PRP increased the formation of tube‐like structures in HUVECs. Co‐treatment of UCB‐MSCs and PRP in a CRWI mouse model increased the wound closure rate and angiogenesis compared with an untreated irradiated group. Moreover, increased expression of VEGF and CD31 were observed in the wound tissue of co‐treated mice compared with untreated irradiated mice. PRP stimulates the release of angiogenic factors from UCB‐MSCs, and combined therapy of UCB‐MSCs and PRP improves regeneration efficacy by enhancing angiogenesis in a CRWI model.